Prevalence of stress among medical students: A comparative study between public and private medical schools in Bangladesh - Mainul, Haque; Eliza Omar, Eva; Md Zakirul, Islam (2015)
Background: Throughout the world all health professionals face stress because of time-pressures, workload, multiple roles and emotional issues. Stress does not only exist among the health professionals but also in medical students. Bangladesh has currently 77 medical colleges 54 of which are private. This study was designed to collect baseline data of stress-level among Bangladeshi students, which we believe will form the basis for further in depth studies.